Tinjauan Yuridis Perbandingan Antara Hukum Positif dan Hukum Islam Terkait Penyalahgunaan Narkoba - Yozzaryo Afandhi; Abdul Haris Kurniawan Jatmiko (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
The phenomenon of drug abuse is increasingly rampant in Indonesia, which sadly is classified as the younger generation. In fact, the demographic bonus in the young age group should have a positive impact on the progress of the nation. However, the reality is the opposite, where the younger generation is increasingly abusing drugs. This study aims to explore more deeply related to drug abuse in the review of positive law and Islamic law. Related to the method used is normative juridical with qualitative analysis. Based on the results of the study, it was found that there are similarities and also differences between positive law and Islamic law, but in general there are many similarities between the two. This study has legal implications that the increasingly rampant drug abuse in Indonesia must be overcome by providing awareness from an early age, providing commendable character education, and also limiting everything that can trigger drug abuse.